A Simple Approach towards Highly Dense Graphene Films for High Volumetric Performance Supercapacitors. Issue 1 (12th January 2022) - Zhao, Xin; Huang, Cong; Tang, Qunli; Hao, Yisu; Zhang, Yan; Hu, Aiping; Chen, Xiaohua
Abstract: An interface self‐assembly followed by hydrothermal reduction method are proposed to obtain a tannic acid (TA)‐modified reduced graphene oxide composite film (|TA/RGO|). This unique method endows |TA/RGO| with several advantages: (1) TA is adopted as a redox‐active spacer between adjacent interlayers for enlarging the ion‐accessible area and contributing to pseudocapacitance; (2) due to the intensive pressure exerted by the sandwich‐like device during the hydrothermal reduction process, appropriate expansion and a relatively flat layered structure are achieved which will facilitate the ion transport. As a result, the |TA/RGO| film shows an ultrahigh volumetric performance of 701 F cm −3 with a high density of 1.91 g cm −3 using a three‐electrode system. When assembled into a symmetric supercapacitor, |TA/RGO| film delivers a high volumetric capacitance of 244.8 F cm −3 and a high capacitance retention of 100 % after 5000 cycles at the current density of 2 A g −1, showing a great potential for large‐scale application. Abstract : Boosting the performance : The grafting of tannic acid (TA) onto the graphene film is prepared through a simple interface self‐assembly followed by hydrothermal reduction process. The obtained tannic acidmodified reduced graphene oxide composite film shows a high density of 1.91 g cm −3 and exhibits an ultrahigh volumetric performance.